Pengembangan Media Pembelajaran Interaktif Berbasis Ispring Suite Pada Mata Pelajaran Matematika Materi Bangun Datar Kelas III Di SDN Mangunharjo 1 Kota Probolinggo - ., Bherlianna Emas Susilo; ., Didit Yulian Kasdriyanto; ., Faridahtul Jannah (CV. ITTC INDONESIA, 2023)
Currently there are many learning media using the internet, ranging from simple to complex, one of which is the Ispring Suite. Ispring suite can be used as an application, HTML5, record video, combine images, as well as a quiz maker. It is hoped that with the ispring suite-based interactive learning media it is hoped that it can help teachers and students understand the flat shape material. The research method used is Research and Development (R & D) proposed by Borg & Gall. In its application, there are ten steps in the implementation of development according to Borg & Gall. However, due to limited manpower, time and costs, the researchers simplified it into 5 development models by taking into account the main focus on the selected stages, namely research reviews and small-scale research. The following are the 5 stages, namely Preliminary Study, Design of interactive learning, product development, Validation and limited trials and Revision of the final product in development. Based on the results of the assessment of learning media experts, it can be concluded that the media is said to be very feasible but with revisions. Suggestions or input from the validator is that the bad songs should be removed during the presentation of the material, the font should be enlarged, as well as images that do not need to be deleted or minimized so as not to distract the students' focus.